APPLICATION OF OBJECTIVE MATRIX (OMAX) METHOD FOR MEASURING PRODUCTIVITY OF PROL TAPE PROCESSING IN UD PURNAMA JATI - Dhanang Eka Putra; Khanifatul Maula Mursid (Department of Food Science and Biotechnology, Faculty of Agriculture Technology, Universitas Brawijaya, 2021)
The main motivation of this research is to see the level of productivity in prol tape production division of UD. Purnama Jati. in order to increase the prol tape productivity with the Objective Matrix (OMAX) method. The research also performed by evaluating the worst performance ratio with the Traffic Light System. The result shows that the measurement period in June 2019 with a productivity index value of 118% being the highest productivity index value. Meanwhile, the lowest productivity occurred in the period of July 2019 with a productivity index of (âˆ’47.89%). Based on the evaluation results of utilizing the Traffic Light System technique, the ratio at the level of